From conception to childhood: Anthropometric characteristics of children conceived by assisted reproductive technologies in Kazakhstan. - Nurgaliyeva , Zhanar; Ilmuratova, Sevara; Кеmelbekov Каnatzhan; Lokshin, Vyacheslav; Zhubanysheva, Karlygash; Izhanova, Aigyul; Umbetyarova , Lyazzat; Seisebayeva, Roza; Tukbekova, Bibigul; Manzhuova, Lyazat; Ussenova, Takhmina (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: As assisted reproductive technologies (ART) expand globally and in Kazakhstan, mon-itoring the long-term health of resulting offspring has become a public health priority. This study aimed to compare growth patterns and anthropometric characteristics in children under five years old born after ART versus natural conception (NC) to under-stand the influence of different conception modes. Methods: A retrospective analysis was conducted on 120 ART-conceived children and 132 NC children, with measurements standardized using WHO weight-for-age, height-for-age, and weight-for-height charts.. Results: Results indicated that preterm births were 4.56 times more frequent in the ART group (95% CI: 2.06–10.07), contributing to a significantly higher incidence of low birth weight (p=0.004). Additionally, mothers in the ART group exhibited significantly higher BMI and weight compared to NC mothers (p<0.001). However, after age and sex standardi-zation, no statistically significant differences in anthropometric indicators were found between NC and ART groups, nor between frozen and fresh embryo transfer cohorts. While the ART group showed a higher percentage of overweight children (8.3% vs. 4.5%), this was not statistically significant. Conclusions: We conclude that ART is generally safe regarding physical development, as initial perinatal disparities tend to normalize by early childhood.